Eslicarbazepine acetate response in intellectual disability population versus general population. (24th November 2020) - Allard, Jon; Lawthom, Charlotte; Henley, William; Mclean, Brendan; Hudson, Sharon; Tittensor, Phil; Rajakulendran, Sanjeev; Ellawela, Shan; Pace, Adrian; Shankar, Rohit
Abstract : Background: A quarter of people with intellectual disability (ID) have epilepsy, compared to approximately one in a hundred across the general population. Evidence for the safe and effective prescribing of antiepileptic drugs (AEDs) for those with ID is, however, limited. Aims of Study: This study seeks to strengthen the research evidence around Eslicarbazepine Acetate (ESL), a new AED, by comparing response of individuals with ID to those from the general population who do not have ID. Methods: A single data set was created through retrospective data collection from English and Welsh NHS Trusts. The UK‐based Epilepsy Database Research Register (Ep‐ID) data collection and analysis method were used. Results: Data were collected for 93 people (36 ID and 57 'no ID'). Seizure improvement of '>50%' was higher at 12 months for 'no ID' participants (56%), compared to ID participants (35%). Retention rates were slightly higher for those with ID (56% compared to 53%). Neither difference was significant. Conclusions: Tolerance and Efficacy for ID and 'no ID' people in our data set were similar. Seizure improvement and retention rates were slightly lower than that found in other European data sets, but findings strengthen the evidence for the use of ESL in the ID population.